Glioma‐derived galectin‐1 regulates innate and adaptive antitumor immunity. Issue 4 (4th September 2013) - Verschuere, Tina; Toelen, Jaan; Maes, Wim; Poirier, Françoise; Boon, Louis; Tousseyn, Thomas; Mathivet, Thomas; Gerhardt, Holger; Mathieu, Veronique; Kiss, Robert; Lefranc, Florence; Van Gool, Stefaan W.; et al.
<x xml:space="preserve">Abstract</x> Galectin‐1 is a glycan‐binding protein, which is involved in the aggressiveness of glioblastoma (GBM) in part by stimulating angiogenesis. In different cancer models, galectin‐1 has also been demonstrated to play a pivotal role in tumor‐mediated immune evasion especially by modulating cells of the adaptive immune system. It is yet unknown whether the absence or presence of galectin‐1 within the glioma microenvironment also causes qualitative or quantitative differences in innate and/or adaptive antitumor immune responses. All experiments were performed in the orthotopic GL261 mouse high‐grade glioma model. Stable galectin‐1 knockdown was achieved via transduction of parental GL261 tumor cells with a lentiviral vector encoding a galectin‐1‐targeting miRNA. We demonstrated that the absence of tumor‐derived but not of host‐derived galectin‐1 significantly prolonged the survival of glioma‐bearing mice as such and in combination with dendritic cell (DC)‐based immunotherapy. Both flow cytometric and pathological analysis revealed that the silencing of glioma‐derived galectin‐1 significantly decreased the amount of brain‐infiltrating macrophages and myeloid‐derived suppressor cells (MDSC) in tumor‐bearing mice. Additionally, we revealed a pro‐angiogenic role for galectin‐1 within the glioma microenvironment. The data provided in this study reveal a pivotal role for glioma‐derived galectin‐1 in the regulation of myeloid cell accumulation within the glioma microenvironment, the most abundant immune cell population in high‐grade gliomas. Furthermore, the prolonged survival observed in untreated and DC‐vaccinated glioma‐bearing mice upon the silencing of tumor‐derived galectin‐1 strongly suggest that the in vivo targeting of tumor‐derived galectin‐1 might offer a promising and realistic adjuvant treatment modality in patients diagnosed with GBM.